The association between the sense of control and depression during the COVID-19 pandemic: a systematic review and meta-analysis - Msetfi, Rachel M.; Kornbrot, Diana E.; Halbrook, Yemaya J. (Frontiers in Psychiatry, 2024)
Introduction High levels of depression and low sense of control have been reported during the COVID-19 pandemic. The removal of typical freedoms through public health restrictions may have played an important role. The aim of this review was to examine data collected during the pandemic and (1) estimate the strength of the association between sense of control and depression, (2) examine whether the different types of control measures affected the strength of the association, and (3) whether this changed as a function of pandemic indicators. Methods We conducted a systematic review and meta-analysis of studies published in English between December 2019 and November 2022. A total of 993 articles were identified, of which 20 were included in the review and 16 in the meta-analysis after conducting a quality assessment using the standard NIH tool. Results The control–depression association gave a bias-independent pooled effect size of r = .41, and grew stronger over the 130 weeks covered by this review but did not change as a function of local COVID incidence rates. Subgroup analyses showed that external and overall control were more strongly related to depression than internal control. Discussion These findings emphasize that external factors are important to the sense of control and the importance of preserving the sense of control in situations where the removal of personal freedoms is necessary, such as public health emergencies.